Preparing our greatest team:The design and delivery of a preparation camp for the London 2012 Olympic Games - Arnold, R.; Hewton, E.; Fletcher, D. (Sport, Business and Management, 2015)
This study investigated the factors perceived to be associated with the design and delivery of an effective Olympic Games preparation camp. To identify and explore such factors, interviews were conducted with eight members of a preparation camp delivery team for the London 2012 Olympic Games, and with two athletes who had participated in Olympic preparation camps.The results identified four overarching factors that should be considered when designing and delivering an effective Olympic preparation camp: planning, operations, environment, and the delivery team. To illustrate the interrelationships between these factors and situate them within the holistic preparation camp context, an operational model was developed. This model also portrays the chronological ordering of events, individuals involved at each stage, and athlete-centered nature of an Olympic preparation camp. Evidence-based recommendations are also provided for those tasked with the design and delivery of an Olympic preparation camp , so that they can optimally prepare athletes and teams for an Olympic Games.